Carvão para seus olhos tocarem: uma poética do deslocamento - Figueiredo, Ruy Cézar Campos (2018)
It is proposed as a research an experience of a poetics of displacement, by means of an engagement in the creative process of Coal For Your Eyes to Touch, an unfolding of artworks evolving performance with multi-screen cinematographic installation. Methodologically inspired in film studies approaches on tactility, performance-as-research approaches on landscape and an appropriated approach of ethnography on sensoriality, the experience promotes 1) contact with mineral coal found at the landscape of Pecém, Ceará, where its dust affects bodies, communities and the environment; 2) contact with the narratives of displacement by communities affected in the area by coal dust and by the whole logic of displacement applied in developing or sub developed countries like Brazil; 3) contact with the flow of this coal back to its place of origin, in La Guajira, north of Colombia. For doing it, discusses environmental and geological aspects related with coal; presents approaches that contemporarily relate art, environment and ecology; contextualize elements and objects created for the realization of the developed performances in dialogue with Helio Oiticica’s Bólides, Parangolés and Quase-Cinemas, and also with Vilém Flusser and Eduardo Oliveira approach on masks; situates in relation with a theory of displacement and resettlement the narratives collected through testimonials of community members from one community in Ceará and another one in La Guajira; calls attention to definitions and approaches of contemporary expanded cinema and multi-screen cinematographic installations, that dialogue with discussions of contemporary geography around place, space and displacement. It is expected, with these ways, to create an experience of displacement that takes into consideration art knowledge as nomadic, embodied and emplaced, exploring the formal possibilities of performance with multi-screen cinematographic installations to create a space of ecocritical contextualization of mineral coal related problems found in a point of Brazilian northeast and produced in a point of Colombian Caribbean, valuing the narratives of communities affected by such problematics.